ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM MENJATUHKAN HUKUMAN TERHADAP TINDAK PIDANA PERJUDIAN SECARA ONLINE (Studi Putusan 121/Pid.B/2012/Pn Gst) - Irfan Gaurifa (Jurnal Panah Hukum, 2022)
The crime of gambling is betting on purpose, namely risking a value or something that is considered valuable by being aware of certain risks and expectations in game events, matches, competitions and events that have no and or uncertain results. The type of research used is normative juridical. The research approach method used is the statute approach, the case approach, and the conceptual approach. The data collection technique used is through descriptive research with a qualitative approach, then the data analysis is carried out as a whole and systemically together with data collection based on the symptom units studied. B/2012/Pn-Gst) was not correct in making the decision, the judge sentenced the defendant to a prison sentence of 3 (three) months, did not impose the sentence as stipulated in Article 303 bis paragraph (1) 1 of the Criminal Code Jo. UU no. 7 of 1974 concerning Gambling Control with the threat of imprisonment for 4 (four) years and a maximum fine of ten million rupiah. The researcher's suggestion is that the judge must be careful in making a decision, based on existing provisions and looking at the facts in court so that it can burden the defendant to admit and regret his actions so that the decision taken is a decision that is able to provide a sense of justice for each party